Public planning in citizen security in the city of Lima, Peru during the years 2020-2024 - Gonzáles-Mejía, Alvaro F. (2025)
The study aimed to analyze the consequences of public planning on citizen security in the city of Lima, Peru, during the years 2020-2024. It seeks to contribute to describing the reality in which citizens of low socioeconomic status are vulnerable to the rising wave of crime. It also aims to present another perspective, ranging from the State's errors to people's distrust of their authorities. The methodology used was qualitative, exploratory, and documentary, which allowed the topic to be defined jointly through a research question. Subsequently, reliable sources were sought and information compiled. In conclusion, beyond the difficult times the country is going through in terms of public planning and citizen security, a new path may be found through the appropriate use of intelligence and counterintelligence, the formalization of informal businesses, and the training of all local governments.